Performance of eight predictive models for hepatocellular carcinoma recurrence after liver transplantation: A comparative study - Ajacio Bandeira de Mello Brandão; Santiago Rodriguez; Cláudio Augusto Marroni; Alfeu de Medeiros Fleck Junior; Matheus V. Fernandes; Marcos Mucenic (Annals of Hepatology, 2024)
Introduction and Objectives: Liver transplantation is the optimal treatment for patients with early hepatocellular carcinoma and cirrhosis. However, hepatocellular carcinoma recurs in approximately 15 % of individuals. This study aimed to assess the efficacy of predictive models for hepatocellular carcinoma recurrence after liver transplantation. Patients and Methods: This retrospective study included 381 patients with HCC and evaluated the performance of the following models: R3-AFP score, alpha-fetoprotein (AFP) model, University of California, Los Angeles (UCLA) nomogram, Pre-Model of Recurrence after Liver Transplantation (MORAL), Post-MORAL, and Combo MORAL models, Risk Estimation of Tumor Recurrence (RETREAT) model and Platelet to Lymphocyte Ratio (PLR) model. Results: The R3-AFP score, UCLA nomogram, AFP model, RETREAT, Combo MORAL, and Post-MORAL models exhibited comparable AUROCs, ranging from 0.785 to 0.733. The AUROCs for the R3-AFP model and AFP model were superior to those of the Pre-MORAL and PLR models. The UCLA nomogram, RETREAT score, Combo MORAL model, and Post-MORAL model performed similarly to the first two models, but were only superior to the PLR model. Conclusions: The R3-AFP model, UCLA nomogram, AFP model, RETREAT, Combo MORAL, and Post-MORAL models demonstrated a moderate predictive capacity for hepatocellular carcinoma recurrence following transplantation. No significant differences were observed among these models in their ability to predict recurrence.